Diseño de la documentación de un sistema de gestión de calidad en el colegio Nuestra Señora de las Mercedes de Piñuelas bajo los requerimientos de la norma ISO 9001 2015. (2021)
Throughout history, quality has been a determining factor that generates an added value in any type of market, that is why having a quality management system has become an indispensable tool in any type of company, taking into account the demands that every day are higher and the competition is more fierce. Currently in Colombia the quality management system in the educational sector is not implemented in as many institutions as it should be, possibly the reason for this is that the managers of these institutions do not know how to do it and ignore its importance; which in short from the point of view that Colombia is in a constant growth where its economy will be reflected in the future according to the quality of education that is managed. The implementation of the Quality Management System within the educational institutions becomes a guide to potentiate productivity and competitiveness, contributing to the formative and administrative management aimed at innovating and improving the educational management. The quality of education in Colombia has always presented deficiencies in its management systems, this has caused delays in continuous improvement, and this directly affects the development of all countries. This is why for the Institución Educativa Departamental Agropecuaria Nuestra Señora De las Mercedes and for any other educational institution it is necessary to implement a quality management system because it allows visualizing the institution as an interrelation and a set of processes, with a final objective of providing a quality educational service, taking into account all the areas of the institution as sections necessary for its operation.